Social adaptation toward climate change among harum manis mangoes growers and agricultural extension activities in Perlis - Kamal Bashah, Muhd Ariff Edzham (2017)
Climate change is proven to have impacted the agricultural productivity, crop choice, and food security everywhere in the world. However, in agriculture there is a way on how to adapt with the climate change. The mango named “Harum Manis” is a famous agricultural product of Perlis, Malaysia. This fruit only produce in Perlis. By suitable adaptation, it will increase the quality and quantity of the fruits. The demand for the fruit is very high. It also contributed to one of the attractions for tourists to visit the country of Perlis. It contributes to agro-tourism in the state of Perlis. Besides, it makes local branding to Perlis. It provides income to small farmers in the state of Perlis. However, the problem arise for the last seasons are decrease in yield because of the climate change or more specific are El Nino. The general objective of this study is to identify social adaptation towards climate change among Harum Manis growers. The specific objectives are to examine the perception level of respondents towards the impacts climate change and also to determine the relationship between socio demographic factor and perception level of mangoes growers toward their social adaptation to climate change and assessing the perception level of the agricultural extension activities. A questionnaire form was constructed to collect data for this study. This study will be a questionnaire survey to 150 growers in Perlis. The expected result for this study are the perception level of respondents toward the impacts of climate change is moderate and there are significant relationship between socio demographic factors (farm size, age, education level, and income) and perception level of mangoes growers toward their social adaptation of climate change impacts. Data that is collected will be processed by using Statistical Package for the Social Science (SPSS) using descriptive, Chi- Square and correlation analysis. The study found that the majority that involves in this industry were grower age range between 51 to 70 years old. Most of grower were Malay and educated up to Highest Malaysian Certificate of Education (STPM) or Skill Certificates. Most of them have incomes up to RM 40000 per season and have been involved in harum manis farming for about 6 to 10 year. From the analysis made, found out that there are moderate level respondent’s perception toward Harum Manis cultivation activity. Furthermore, from the result, majority of respondents were at moderate level perception on social adaptation towards impact of climate change. The result shows the total mean is 3.92 that is consider as a high level on perception or view of the risks of climate change. 73.3% of respondents in a high level of perception or view of the risks of climate change while only 26.7% of respondents in a moderate level of perception or view of the risks of climate change. From that, 100% of the respondents were taking action watering their crops more frequently in adaptation in their agricultural activities in the face of climate change/disaster. Then followed by 6.7% of the respondents choose to do crop diversification, planting more shade trees and implementing soil conservation techniques respectively. The growers also take solution in overcoming the problem of climate change/natural disaster. 100% of the respondents choose to take a good manage for plant and irrigation. Majority of respondents were at moderate level on perception toward agricultural agency and extension program. From the correlation analysis, the result shows a correlation between socio demographic profiles with respondent perception toward climate change. Only education level have positive correlation. Next, respondents perception towards agricultural extension activity shows that respondent’s experience in agriculture farming, average total yield per season and net income per season age have a relationship between respondents perceptions toward agriculture extension activity (agency and agricultural officer). Agricultural Department play an important roles to assist farmer in manage their Harum Manis farm. Most farmers are depending to agricultural officer in order to guide them to be a successful farmer. From this study, a conclusion can be made that the Harum Manis growers easy to adapt to climate change that happened. Most growers already involved in farming for more than 10 years. Various methods have been developed and adapted to prevailing circumstances. However, what happened for the last season is unexpected. This cause the decreased of the yields. But, for the extension activities or services, the authorities must take this issue seriously. This is because, from the results, it shows the extension activities and services at the moderate level. Harum Manis planting activities should be in line with the services and agricultural extension programs. This will ensure that agricultural activity is widely regarded in Perlis.